Mast cells in renal inflammation and fibrosis: Lessons learnt from animal studies. Issue 1 (January 2015) - Madjene, Lydia Celia; Pons, Maguelonne; Danelli, Luca; Claver, Julien; Ali, Liza; Madera-Salcedo, Iris K.; Kassas, Asma; Pellefigues, Christophe; Marquet, Florian; Dadah, Albert; Attout, Tarik; El-Ghoneimi, Alaa; et al.
Highlights There is a considerable mast cell infiltrate in kidneys in renal inflammatory disease in humans. Examinations in mast cell or mast cell protease deficient mouse models are discussed. These reveal a highly contrasting picture with both beneficial and disease aggravating actions. Sometimes the action of mast cells differs from the one observed with a mast cell protease suggesting that mast cell mediators released at the same time can have opposite activities.